PENGARUH INFLASI DAN NILAI TUKAR TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Nur, Meilani; Ayunda Rahmawati, Dayyinah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
This study aims to examine the impact of inflation and exchange rates on Indonesia’s economic growth, both individually (partially) and collectively (simultaneously). The research utilizes time series data spanning from 2008 to 2019. To analyze the relationship between these variables, multiple linear regression analysis is employed, complemented by tests for the coefficient of determination and statistical significance using t-tests and F-tests, all conducted through the SPSS 24 software. The findings indicate that inflation exerts a negative and statistically significant influence on Indonesia’s economic growth, suggesting that higher inflation tends to suppress economic expansion. Meanwhile, the exchange rate also has a negative effect on economic growth, but this relationship is statistically insignificant, implying that fluctuations in the exchange rate may not be a primary determinant of economic performance in Indonesia. Furthermore, the coefficient of determination test results reveal that inflation and exchange rates collectively account for 48.12% of the variations in Indonesia’s economic growth, meaning that nearly half of the changes in economic growth can be explained by these two variables, while the remaining portion is likely influenced by other factors. The results of the F-test further confirm that when considered together, inflation and exchange rates significantly impact economic growth in Indonesia. This study highlights the importance of maintaining economic stability by managing inflation and monitoring exchange rate fluctuations, as they can have direct and indirect effects on the country's overall economic performance.